2017
DOI: 10.1111/jth.13607
|View full text |Cite
|
Sign up to set email alerts
|

One amino acid in mouse activated factor VII defines its endothelial protein C receptor (EPCR) binding and modulates its EPCR‐dependent hemostatic activity in vivo

Abstract: Background Human activated factor VII (hFVIIa), which is used in hemophilia treatment, binds to the endothelial protein C (PC) receptor (EPCR) with unclear hemostatic consequences. Interestingly, mice lack the activated FVII (FVIIa)-EPCR interaction. Therefore, to investigate the hemostatic consequences of this interaction in hemophilia, we previously engineered a mouse FVIIa (mFVIIa) molecule that bound mouse EPCR (mEPCR) by using three substitutions from mouse PC (mPC), i.e. Leu4→Phe, Leu8→Met, and Trp9→Arg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Although earlier studies suggest that FVIIa-EPCR interaction may contribute to the hemostatic effect of FVIIa in hemophilia therapy, 5;14;20 it is not entirely clear the mechanism by which EPCR-FVIIa interaction contributes to the hemostatic effect. EPCR-FVIIa interaction could contribute to the hemostatic effect of FVIIa by competing with protein C for the EPCR and thus downregulating EPCR-mediated APC generation, 1;5;19 by FVIIa-EPCR directly activating FX, or by EPCR tethering of FVIIa on the endothelium thus extending the locale of procoagulant reactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although earlier studies suggest that FVIIa-EPCR interaction may contribute to the hemostatic effect of FVIIa in hemophilia therapy, 5;14;20 it is not entirely clear the mechanism by which EPCR-FVIIa interaction contributes to the hemostatic effect. EPCR-FVIIa interaction could contribute to the hemostatic effect of FVIIa by competing with protein C for the EPCR and thus downregulating EPCR-mediated APC generation, 1;5;19 by FVIIa-EPCR directly activating FX, or by EPCR tethering of FVIIa on the endothelium thus extending the locale of procoagulant reactions.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that the differences between human and murine FVIIa to interact with murine TF or EPCR alone were the reasons for this discrepancy since murine FVIIa variants that effectively interact with both TF and EPCR were also used at 3 mg/Kg dose to restore hemostasis in hemophilia B mice. 14;20 The restoration of hemostasis in FVIII Ab-induced hemophilia, where the bleeding phenotype is not as severe as in FVIII genetic deficient mice (FVIII −/− mice) because of residual FVIII activity in the Ab-induced hemophilia model, required 4 to 10 times less rFVIIa (0.25 to 1 mg/Kg) than necessary in FVIII −/− mice (1 to 10 mg/Kg).…”
Section: Discussionmentioning
confidence: 99%
“…This analog exhibited a 3‐fold increase in hemostatic activity compared with wild‐type mFVIIa . More recently, the L4F substitution was found to be solely responsible for the EPCR‐dependent increase in hemostatic activity . They concluded that binding to EPCR on the endothelium may augment the procoagulant effect of FVIIa.…”
Section: Discussionmentioning
confidence: 99%
“…Pavani et al . suggested a direct role for EPCR in FVIIa‐mediated hemostasis . They engineered a murine FVIIa (mFVIIa) analog with three mutations (L4F/L8M/W9R) that allow it, unlike wild‐type mFVIIa, to bind murine EPCR.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant rat FVIIa was purified exclusively in a 2-chain form (Figure 1B), similar to what we previously observed with human, mouse, and canine FVIIa engineered transgenes. 12,14,[17][18][19] Using a prothrombin time (PT) clotting assay, we found that rat FVIIa tissue factor-dependent activity was similar to rhFVIIa (Figure 1C; P . .05).…”
Section: Purification Of Rat Fviia and In Vitro Activitymentioning
confidence: 99%